PENGARUH FAKTOR FUNDAMENTAL DAN FAKTOR EKONOMI MAKRO PADA RETURN SAHAM PERUSAHAAN CONSUMER GOOD DI BURSA EFEK INDONESIA - Yulita Asri, I.G.A Amanda; Suwarta, I Ketut (E-Jurnal Akuntansi; Vol 8 No 3 (2014), 2014)
This study aims to determine the effect of fundamental factors (assets growth, Total Asset Turn Over, and firm size) and macro economic factors (inflation and interest rates) on stock returns Consumer Good companies listed on the Stock Exchange in the period 2008-2011. The collection of samples was done by purposive sampling method and obtained 48 samples. This study used multiple linear regression analysis techniques. The analysis showed that all independent variables simultaneously significant effect on stock returns. Partially, it was found that only Total Asset Turn Over and inflation have a significant effect on stock returns, while the asset growth variable, firm size, and the interest rate showed no significant effect on stock returns.
Keywords: stock returns, fundamentals, macro economy.